Optical soliton solutions of the NLSE with quadratic-cubic-Hamiltonian perturbations and modulation instability analysis - Aslan, Ebru Cavlak (Elsevier Gmbh, 2019)
The aim of this paper is to present optical soliton solutions of the nonlinear Schrodinger equation. Here, the quadratic-cubic nonlinearity in the existence of Hamiltonian perturbations is considered. The Jacobi elliptic ansatz method is applied to obtain the optical soliton solutions. As a result, dark, bright and w-shaped optical soliton are obtained. Additional, the modulation instability analysis is given.
Keywords: NLSE; Jacobi elliptic ansatz method; Optical soliton